Metal complexes as radical initiators inducing Antioxidant/prooxidant activity of phenols/polyphenols of food, and their evaluation as anticancer agents - Drouza, Chryssoula; Spanou, Smaragda (My University, 2023)
Phenolics are activated by VV and/or VIV coordinated catalytic sites in the lipophilic matrix of oil mediated by dioxygen activation; in this oxidative environment free radicals are trapped by -tocopherol to give -tocopheryl radicals monitored by X-band cw-EPR vs time providing very useful quantification tool for the determination of the ability of the complexes to initiate radicals1.The possibility to quantify α-Tocopherol in extra virgin olive oils by EPR spectroscopy has been investigated using vanadium (V) lipophilic metal complexes as radical initiators1. The experimental results showed that there is a relationship between the intensity of the signal of the α-Tocopheryl radical in the EPR spectrum and the concentration of α-Tocopherol contained, upon addition in food samples The α-Tocopherol concentration values determined for the olive oils were validated by comparison with those determined by the 19F NMR method2. The metal-based radical initiators have also been applied for the investigation of the phenol/polyphenol content conducted through spin trapping on -tocopheryl radicals, whereas, parameters associated to the nature of the phenolic compound and their prooxidant/antioxidant activity are determined through the kinetics of the radical initiation through O2 activation reactions. Anticancer properties of these complexes are evaluated. References [1] Drouza, C., Dieronitou, A., Hadjiadamou, I., & Stylianou, M. (2017). Investigation of Phenols Activity in Early Stage Oxidation of Edible Oils by Electron Paramagnetic Resonance and19F NMR Spectroscopies Using Novel Lipid Vanadium Complexes As Radical Initiators. Journal of Agricultural and Food Chemistry, 65(24), 4942-4951. https://doi.org/10.1021/acs.jafc.7b01144. [2] C. (2022). Binuclear VIV/V, MoVI and ZnII - hydroquinonate complexes: Synthesis, stability, oxidative activity and anticancer properties. Journal of Inorganic Biochemistry, 235, 111911. https://doi.org/https://doi.org/10.1016/j.jinorgbio.2022.111911. [3] Vlasiou, M., & Drouza, C. (2015). 19F NMR for the speciation and quantification of the OH-molecules in complex matrices. Analytical Methods, 7(9), 3680-3684. https://doi.org/10.1039/C5AY00178A.
Keywords: anticancer; metal complexes; olive oil; EPR; tocopheryl radical